(untitled) (Journal of the College of Education for Women, 2019)
The phenomenon of spatial variation in the economic, social and urban development levels is considered prevalent in most of the economic and social systems,this relates to the concentration of most of those activities in certain regions and because of their rarity in other regions , that led to the emergence of the problem of the sharp contrast between the most developed areas and least developed areas within the same region or within the regions of the same country,Reduction of this variables , in addition to the development of areas through following up and relying on an effective regional development enabling to reduce unemployment as well as to stop the migration of the unplanned for population,And the ideal use of available materials and the potential one in these areas, with the establishment of effective economic activities, especially , the establishing various industries ,in addition to the development of infrastructure , which reflects and represents the the important aspects in spatial ability and efficiency in attracting the economic and social activities.Furthermore , the study area has a certain specificity represented as an agricultural area and this gave an exceptionally interesting when implementing any planning process.Therefore, the study has focused on the most important concepts of spatial-economic )The concept of structure and concept of spatial structure)